Deglacial record of palaeoearthquakes interpreted from mass transport deposits at three lakes near Rouyn‐Noranda, north‐western Quebec, Canada. Issue 7 (25th May 2018) - Brooks, Gregory R.
Abstract: As part of an investigation of deglacial palaeoseismology within an intracratonic region of north‐eastern North America, the compilation of sub‐bottom acoustic profile surveys from study areas at Duparquet and Dufresnoy lakes, north‐western Quebec, Canada, produced thirteen and eight event horizon maps, respectively, depicting subaqueous mass transport deposits that are interbedded within Lake Ojibway glaciolacustrine varve deposits. Analysis of rhythmic couplets recovered in cores from both locations yielded varve ages with annual resolution for the event horizons relative to the regional Timiskaming varve series. These results are integrated with the published event horizon stratigraphy and varve chronology from nearby Lac Dasserat. The combined event horizon records for the three lakes overlap between varve years 1175 to 1625 (9395 to 8945 ± 200 cal yearbp ) and consist of 26 event horizons. Fifteen event horizons are inferred to be evidence of 11 palaeoearthquakes at qualitative levels of interpretative confidence varying from high to low. The palaeoearthquake interpretations and assessments of interpretative confidence are made from weightings of the event horizon signatures and, where possible, evidence supporting a stratigraphic footprint extending beyond a given study area. Occurring over a 450 varve year period when rapid crustal uplift was still underway, 11 interpreted palaeoearthquakes happened at an average rate of every ca 40 years. Relative to a published minimum threshold magnitude for generating a recognizable geomorphic signature, this average rate of occurrence exceeds the modern return period by two orders of magnitude. The palaeoearthquakes probably occurred within a period of elevated seismicity associated with rapid crustal unloading during deglaciation.